Epidemiology of ectopia lentis and outcomes after surgery in a Danish population. Issue 12 (December 2022) - Rasul, Asrin; Roos, Laura; Groth, Kristian; Riise, Per; Bach-Holm, Daniella; Kessel, Line
Abstract : The main reason for ectopia lentis was Marfan syndrome, which could be genetically confirmed in 70.5%. Surgery was safe and improved visual acuity. Abstract : Purpose: To describe the causes of ectopia lentis (EL) and the outcomes after surgery in a Danish population. Setting: The Eye Clinic Rigshospitalet and Kennedy Center in Copenhagen. Design: Retrospective cohort study. Methods: Medical records of patients with nontraumatic EL born after 1980 and seen at the Eye Clinic Rigshospitalet and Kennedy Center from 1983 to 2019 were reviewed. Clinical information regarding family history, comorbidities, genetic workup, ophthalmological examinations, and surgical history was retrieved. Results: 72 patients (38 males), of whom 68 had bilateral EL (94.4%) were identified. Marfan syndrome (MFS) was found in 34 (47.2%) and biallelic variants in ADAMTSL4 in 4 (5.6%). Surgery was performed in 38 (52.8%) patients, 66 eyes, with a median age at the time of first eye surgery of 8.4 years (range 0.8 to 39.0 years) and a follow-up of 2.3 years (range 0 to 25.7 years). Intraocular lenses were implanted in 9 (23.7%) (11 eyes). Corrected distance visual acuity improved from 0.7 to 0.2 logMAR (median) in right eyes and from 0.7 to 0.3 logMAR in left eyes postoperatively. 21 patients (56.8%), 42 eyes, did not experience any surgery-related complications. 3 patients (3 eyes) experienced a perioperative tear in the posterior capsule. Temporary postoperative ocular hypertension was reported in 3 patients (7.9%) (3 eyes), and 2 patients (5.4%) (2 eyes) developed persistent ocular hypertension. There were no cases of postoperative retinal detachment. Conclusions: The main reason for EL was MFS. Surgery improved visual acuity, and postoperative ocular hypertension was the most common complication, whereas retinal detachment was not observed.